Inhibition and Rescue of Hyperglycemia‐Induced Cellular Senescence by Mitochondrial Transfer from Enucleated Mesenchymal Stem Cell‐Derived Microvesicles for Chronic Wound Healing - Zixuan Dong; Xiaobing Liu; Shichun Li; Xiaoling Fu (Advanced Science)
Abstract The aberrant cellular senescence in chronic wounds presents a significant barrier to healing. Mitochondrial dysfunction is critical in initiating and maintaining cellular senescence, underscoring therapeutic potential in restoring mitochondrial function by delivering healthy mitochondria to wound cells. However, approaches for delivering mitochondria to achieve optimized wound repair remain lacking. Herein, enucleated MSCs‐derived microvesicles containing functional mitochondria (Mito@euMVs) via simple extrusion are developed. By controlling the size of microvesicles within a small micron‐scale range, the mitochondrial encapsulation efficiency is optimized. Mito@euMVs effectively delivered mitochondria into fibroblasts and HUVECs, inhibiting and rejuvenating hyperglycemia‐induced cellular senescence. To enhance the clinical applicability, soluble PVA microneedle patches for the transdermal Mito@euMVs delivery are utilized. In diabetic rats with pressure sores, the senescence‐inhibiting and ‐rescuing properties of Mito@euMVs are further validated, along with their therapeutic efficacy, demonstrating their potential for chronic wound repair. Moreover, as a versatile delivery vehicle for mitochondria, Mito@euMVs hold promising for treating mitochondrial dysfunction and aging‐related conditions.